The effects of Sarconesiopsis magellanica larvae (Diptera: Calliphoridae) excretions and secretions on fibroblasts (2015)
Sarconesiopsis magellanica is a necrophagous blowfly which is relevant in both forensic and medical sciences. Previous studies regarding this species have led to understanding life-cycle, population and reproduction parameters, as well as identifying and characterising proteolytic enzymes derived from larval excretions and secretions (ES). As other studies have shown that ES proteolytic activity plays a significant role in wound healing and fibroblasts play a relevant role in granulation tissue formation during such healing, the present study was aimed at analysing the biological effect of S. magellanica larval ES on fibroblasts. ES were obtained from third-instar larvae and added to fibroblast cells at three concentrations (10, 5 and 1. ?g/mL) to evaluate their behaviour. MTT assays were used for analysing cell proliferation and viability, whilst cell adhesion was measured by optical density with 10% SDS. Fibroblast migration and morphology was recorded by microscopic observation. ES did not affect fibroblast viability and induced an increase in cell proliferation; cell adhesion became reduced, whilst cell migration through extracellular matrix increased. ES also induced a decreased cell surface and morphological alterations. Changes in all the above-mentioned parameters were reduced when ES were incubated at 60. °C, probably due to protease denaturation. These results suggested that the proteases contained in S. magellanica larval ES contributed towards granulation tissue formation, increased cell migration and promoted cell proliferation. All these data support carrying out further experiments aimed at validating S. magellanica usefulness in larval therapy. © 2014 Elsevier B.V.